PENGARUH KUALITAS PRODUK, HARGA, DAN PROMOSI TERHADAP KEPUTUSAN PEMBELIAN PADA ALAT OLAHRAGA SPEEDS SECARA ONLINE DI SIDOARJO - Salsya Faradila; Rizal Yulianto (Fakultas Ekonomi, 2026)
The growing competition in the sports gear market has driven businesses to grasp what impacts consumer buying choices. This research seeks to examine how product quality, pricing, and promotional efforts affect the purchasing choices for Speeds sports items. A quantitative method featuring surveys was used in this study, and the data were analyzed through Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS 3. 0. Findings reveal that price plays the most significant role in shaping purchasing decisions, whereas product quality and promotional efforts have less impact. Consequently, companies ought to adopt suitable pricing strategies, complemented by enhancements in product quality and efficient marketing campaigns.